Evaluation of an ozone slurry ice combined refrigeration system for the storage of farmed turbot (Psetta maxima) - Campos, Carmen Adriana; Losada, Vanesa; Rodríguez, Oscar; Aubourg, Santiago P.; Barros Velázquez, Jorge (Food Chemistry)
The use of ozonised slurry ice was investigated as a new refrigeration system for the storage of farmed turbot (Psetta maxima). With this purpose in mind, an ozone generator device was coupled to a slurry ice system working subzero at −1.5 °C. The ozone concentration was adjusted to a redox potential of 700 mV, and the slurry ice biphasic mixture was prepared at a 40% ice/60% water ratio and 3.3% salinity. Certain biochemical parameters indicative of fish freshness, such as the rate of nucleotide degradation or TMA-N formation, were not significantly affected by the presence of ozone in the slurry ice mixture. However, storage in ozonised slurry ice significantly slowed down the mechanisms responsible for lipid hydrolysis and lipid oxidation in farmed turbot. Storage in ozonised slurry ice also led to significantly (p < 0.05) lower counts of both total aerobes and psychrotrophic bacteria in both turbot muscle and skin, as compared with the control batch stored without ozone. Sensory analyses confirmed an extended shelf life of turbot specimens stored in ozonised slurry ice; these maintaining “A” sensory quality up to day 14, while the counterpart batch stored in slurry ice kept this quality only up to day 7. The combination of ozone and slurry ice may be recommended for the chilling and storage of farmed turbot with a view to extending its shelf-life. Fil: Campos, Carmen Adriana. Universidad de Santiago de Compostela; España. Universidad de Buenos Aires. Facultad de Ciencias Exactas y Naturales. Departamento de Industrias; Argentina. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina Fil: Losada, Vanesa. Consejo Superior de Investigaciones Cientificas; España Fil: Rodríguez, Oscar. Universidad de Santiago de Compostela; España Fil: Aubourg, Santiago P. Consejo Superior de Investigaciones Cientificas; España Fil: Barros Velázquez, Jorge. Universidad de Santiago de Compostela; España